Ovarian Manson's Schistosomiasis: Rare Diagnosis or Underestimated Prevalence? - Gomes, Elainne Christine de Souza; Domingues, Ana Lúcia Coutinho; Aguiar Júnior, Francisco Carlos Amanajás de; Barbosa, Constança Simões (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
The occurrence of Manson's schistosomiasis in organs of the female reproductive tract is an uncommon event, given that the etiological agent for this disease is a blood parasite that inhabits the mesenteric veins. In this case report, a 45-year-old female patient reported that her first symptoms had been strong pain in the left iliac region around two years earlier. An endovaginal pelvic ultrasonography showed that the left ovary was enlarged, and the report suggested that this finding might be correlated with clinical data and tumor markers. After being examined at several healthcare services, the patient was referred to an oncology service due to suspected neoplasia, where she underwent a left ovariectomy. The result from the histopathological examination showed the presence of granulomatous inflammatory processes surrounding both viable and calcified eggs of Schistosoma mansoni. There was no evidence of any neoplastic tissue. The patient was medicated and followed-up as an outpatient.
Keywords: ectopic schistosomiasis; ovarian schistosomiasis; schistosoma mansoni; granuloma; neoplasia